Confronting complexities of artifact–geofact debates: re-analysis of a coarse volcanic rock assemblage from Chilean Patagonia. (2nd April 2016) - Garvey, Raven; Mena, Francisco
Abstract : An assemblage of coarse volcanic rock (CVR) derived from the walls of a rockshelter in Aisén, Chile was recently described as consisting of bifaces, projectile points, and picks [Prentiss et al. 2015a. Lithic Technology 40:112–127]. The objects are not universally accepted as cultural, however, on account of both their crude appearance and the fact that CVR industries have not been previously identified in either the valley where the objects were found or elsewhere in Patagonia. We present the results of three independent studies—a single-blind poll of lithics specialists, on-site assessment of stone availability and natural agents of modification, and protein residue analysis using cross-over immunoelectrophoresis—none of which support a cultural origin for the CVR specimens. We discuss these findings in terms of a more general debate in lithics analysis regarding reconciliation of conflicting evidence and interpretations in ambiguous cases.